2002
DOI: 10.1093/aob/mcf101
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Production, Microsporangium Dehiscence and Pollen Flow in Himalayan Cedar (Cedrus deodara Roxb. ex D. Don)

Abstract: Microsporangium dehiscence, pollen production and dispersal were studied in Himalayan cedar (Cedrus deodara) during 1998 and 1999. Microsporangium dehiscence showed diurnal periodicity and was found to be related to air temperature and relative air humidity, with a strobilus taking 2 d to dehisce completely in warmer conditions and 3 d in cooler ones. The frequency of flowering in C. deodara was highly variable during the two successive years; however, cyclical production of pollen grains was observed in 50% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…Differences among sampling years as well as higher pollen production from lower stations and southern directions are reported for various species (Fotiou et al 2010;Guardia and Belmonte 2004;Jato et al 2007a;McKone 1990;Moe 1998). Plasticity in pollen production is largely manifested under different environmental factors (LaDeau and Clark 2006;Rogers et al 2006;Wan et al 2002;Wayne et al 2002;Ziska and Caulfield 2000) and has been reported for herbaceous and woody species from different climatic zones: for Alnus incana (Moe 1998), Betula alba (Jato et al 2007a), Cedrus deodara (Khanduri and Sharma 2002a), Chionochloa pallens (McKone 1990), O. europaea (Ferrara et al 2007), Parietaria judaica (Fotiou et al 2010;Guardia and Belmonte 2004), Pinus roxburghii (Khanduri and Sharma Corylus avellana 900 m, S 190.2 (±8.0) 5.6 9 10 3 (±1.2 9 10 3 ) 1.1 9 10 6 (±0.1 9 10 6 ) 5.4 9 10 2 (±1.2 9 10 2 ) 0.3 9 10 1 (±0.1 9 10 1 ) 3.2 9 10 6 (±0.8 9 10 6 ) 900 m, N 219.1 (±7.0) 2.7 9 10 3 (±0.5 9 10 3 ) 5.7 9 10 5 (±0.6 9 10 5 ) 1.2 9 10 3 (±0.2 9 10 3 ) 0.5 9 10 1 (±0.1 9 10 1 ) 3.1 9 10 6 (±0.8 9 10 6 ) Cupressus sempervirens var. horizontalis 90 m, plateau 19.9 (±0.3) 1.9 9 10 4 (±0.1 9 10 4 ) 3.8 9 10 5 (±0.2 9 10 5 ) 2.1 9 10 5 (±0.2 9 10 5 ) 1.0 9 10 4 (±0.1 9 10 4 ) 4.0 9 10 9 (±0.5 9 10 9 ) 450 m, plateau 16.3 (±0.3) 2.1 9 10 4 (±0.3 9 10 4 ) 3.3 9 10 5 (±0.3 9 10 5 ) 9.2 9 10 4 (±0.9 9 10 4 ) 5.5 9 10 3 (±0.5 9 10 3 ) 2.0 9 10 9 (±0.3 9 10 9 ) 450 m, S 17.5 (±0.3) 1.8 9 10 4 (±0.2 9 10 4 ) 2.9 9 10 5 (±0.2 9 10 5 ) 1.2 9 10 5 (±0.1 9 10 5 ) 7.1 9 10 3 (±0.3 9 10 3 ) 2.2 9 10 9 (±0.3 9 10 9 ) 450 m, N 17.0 (±0.3) 2.0 9 10 4 (±0.2 9 10 4 ) 3.1 9 10 5 (±0.2 9 10 5 ) 7.4 9 10 4 (±1.2 9 10 4 ) 4.3 9 10 3 (±0.6 9 10 3 ) 1.8 9 10 9 (±0.3 9 10 9 ) Cupressus sempervirens var.…”
Section: Discussionmentioning
confidence: 87%
“…Differences among sampling years as well as higher pollen production from lower stations and southern directions are reported for various species (Fotiou et al 2010;Guardia and Belmonte 2004;Jato et al 2007a;McKone 1990;Moe 1998). Plasticity in pollen production is largely manifested under different environmental factors (LaDeau and Clark 2006;Rogers et al 2006;Wan et al 2002;Wayne et al 2002;Ziska and Caulfield 2000) and has been reported for herbaceous and woody species from different climatic zones: for Alnus incana (Moe 1998), Betula alba (Jato et al 2007a), Cedrus deodara (Khanduri and Sharma 2002a), Chionochloa pallens (McKone 1990), O. europaea (Ferrara et al 2007), Parietaria judaica (Fotiou et al 2010;Guardia and Belmonte 2004), Pinus roxburghii (Khanduri and Sharma Corylus avellana 900 m, S 190.2 (±8.0) 5.6 9 10 3 (±1.2 9 10 3 ) 1.1 9 10 6 (±0.1 9 10 6 ) 5.4 9 10 2 (±1.2 9 10 2 ) 0.3 9 10 1 (±0.1 9 10 1 ) 3.2 9 10 6 (±0.8 9 10 6 ) 900 m, N 219.1 (±7.0) 2.7 9 10 3 (±0.5 9 10 3 ) 5.7 9 10 5 (±0.6 9 10 5 ) 1.2 9 10 3 (±0.2 9 10 3 ) 0.5 9 10 1 (±0.1 9 10 1 ) 3.1 9 10 6 (±0.8 9 10 6 ) Cupressus sempervirens var. horizontalis 90 m, plateau 19.9 (±0.3) 1.9 9 10 4 (±0.1 9 10 4 ) 3.8 9 10 5 (±0.2 9 10 5 ) 2.1 9 10 5 (±0.2 9 10 5 ) 1.0 9 10 4 (±0.1 9 10 4 ) 4.0 9 10 9 (±0.5 9 10 9 ) 450 m, plateau 16.3 (±0.3) 2.1 9 10 4 (±0.3 9 10 4 ) 3.3 9 10 5 (±0.3 9 10 5 ) 9.2 9 10 4 (±0.9 9 10 4 ) 5.5 9 10 3 (±0.5 9 10 3 ) 2.0 9 10 9 (±0.3 9 10 9 ) 450 m, S 17.5 (±0.3) 1.8 9 10 4 (±0.2 9 10 4 ) 2.9 9 10 5 (±0.2 9 10 5 ) 1.2 9 10 5 (±0.1 9 10 5 ) 7.1 9 10 3 (±0.3 9 10 3 ) 2.2 9 10 9 (±0.3 9 10 9 ) 450 m, N 17.0 (±0.3) 2.0 9 10 4 (±0.2 9 10 4 ) 3.1 9 10 5 (±0.2 9 10 5 ) 7.4 9 10 4 (±1.2 9 10 4 ) 4.3 9 10 3 (±0.6 9 10 3 ) 1.8 9 10 9 (±0.3 9 10 9 ) Cupressus sempervirens var.…”
Section: Discussionmentioning
confidence: 87%
“…Khanduri et al (2002) have suggested that the long-distance transport of Pinus roxburghii pollen is easier downhill than uphill. Similarly, transport upstream appears to have been more favored in the present study, prompting an increase in Q. ilex subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Allison, 1990;Khanduri & Sharma, 2002) and angiosperms (e.g. Tormo Molina et al, 1996;Gómez-Casero et al, 2004;Rovira & Tous, 2005) show that pollen production heavily depends on many different factors such as available resources, soil and environmental conditions and varies considerably among anemophilous species.…”
Section: Abstract: Environmental Effect Flower Production Rate Micrmentioning
confidence: 99%